2005
DOI: 10.1071/ah050306
|View full text |Cite
|
Sign up to set email alerts
|

The 'right story' to the 'right person': communication issues in end-of-life care for Indigenous people

Abstract: staff need to be aware of a myriad of crosscultural issues. Although anecdotal evidence indicates that the quality of communication to Aborigines in the health care setting can be extremely varied, there seems to be very little research in this area. This article seeks to address the dearth of information in this area by presenting recent findings from Australian research that developed a model for Indigenous palliative care.The research that has been undertaken on the topic has mostly focused on communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…The findings on cross-cultural fear and incompatibility, which are complex and reported in full elsewhere, 20 can only be noted in this article.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The findings on cross-cultural fear and incompatibility, which are complex and reported in full elsewhere, 20 can only be noted in this article.…”
Section: Resultsmentioning
confidence: 86%
“…As the full findings on communication, which are published elsewhere indicate, 20 effective communication with Indigenous people in the health setting is all about giving "the right story" to the "right person".…”
Section: Defining the Work -Role Concernsmentioning
confidence: 98%
“…As outlined in related publications of further findings from the study, it is essential in working with Aboriginal peoples to communicate the 'right story' to the 'right person' within the community [13]. Also as documented in further findings from the study, respect for cultural traditions of communication with regards to the care of the dying is essential to avoid contributing to the possibility of 'pay back' after the person dies [14].…”
Section: Major Concern -Need Consent From Right Relationshipmentioning
confidence: 83%
“…It was noted that in East Arnhem Land the Jungai is a particularly important person to obtain consent from in regards to body parts, including the cutting of hair. As outlined elsewhere, it is essential in Indigenous health care to speak to the 'right' person within the network of family and community relationships [13,25]. Disrespect for such traditional processes can lead to payback for the ill Indigenous person or their relatives, as well as considerable anger from family members and clinical staff.…”
Section: Discussionmentioning
confidence: 99%
“…54,71 'Cultural interpreters', such as Aboriginal health workers, may also be helpful in providing guidance in cultural norms and facilitating understanding of illness concepts that may be underpinned by completely different worldviews. 90,91 Nonverbal communication is also important. The vast majority of oncology patients prefer face-to-face communication, 9 and randomized controlled trials of physicians' posture whilst breaking bad news have shown patients prefer physicians to sit rather than stand, and perceive those that do so as more compassionate.…”
Section: Style Of Delivery: Verbal and Nonverbal Aspectsmentioning
confidence: 99%